Ambientes e fluxos informacionais: modelo de diagnóstico de interfaces (DIFI) sob a ótica dos valores culturais - Garcia, Regis [UNESP] (2012)
This study presents, from a multidisciplinary theoretical basis, the proposal of the model of Diagnostic of Interferences on Informational Flows (DIIF). In summary, the model recognizes the individual as a cultural being in its relations with informational and organizational cultures in the context of the organizations. It highlights the culture values as the elements which tend to represent culture on a more objective way. It reviews the theories related to informational flows and brings contributions on critical approaches to the Mathematical Theory of Communication. Under the support of these references, it advances, discussing issues about the psychological implications involving stress, coping and the perception of the informational support, from the perspective of interferences in informational flows and of the incongruence between speech and practice under the cultural bias. The DIIF is based and structured into five dimensions: the Cultural Fit (CF); the Informational Values Shared (IVS); the Informational Flows Interference (IFI); the Informational Values Perceived (IVP); and the Psychological Implications (PI). The research question that guides this study is the possibility of developing and validating a diagnostic model, aiming to contribute that the actions of interferences in informational flows from the organizations be based on the preplanning and on the better understanding of individual perceptions. Preliminarily, the instrument was submitted to a pretest with 98 respondents and served to the purposes of validation and adjustments of its components from the use of factor analysis and of reability of scales. In the final implementation, the field research was adopted, applying a structured questionnaire with one opened question and some closed ones, in a sample of 3,299 individuals, from 107,000 undergraduated students from a... (Complete abstract click electronic access below)